EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA MATERI IPAS KELAS V SEKOLAH DASAR - aufaa rihhadatul aisy; Septina Rahmawati; Yoga Awalludin Nugraha; Dhina Cahya Rohim; Moh. Aris Prasetiyanto (STKIP Subang, 2025)
This study aims to analyze the effectiveness of the cooperative learning model Student Team Achievement Division (STAD) on students’ learning interest and achievement in the subject of Integrated Science and Social Studies (IPAS) for fifth-grade students at SD 3 Pedawang. The research employed a quasi-experimental method using a non-equivalent control group design. The participants consisted of an experimental class taught using the STAD model and a control class taught using conventional methods. The research instruments included a learning achievement test and a learning interest questionnaire, both of which met the criteria for validity, reliability, item difficulty, and discrimination power. Data analysis was conducted through normality and homogeneity tests, paired sample t-test, independent sample t-test, and N-Gain calculation. The findings reveal that the implementation of the STAD model significantly improved both students’ learning achievement and interest compared to conventional methods. The average post-test score of the experimental class was higher than that of the control class, with the improvement categorized as moderately effective based on the N-Gain results. Furthermore, students in the experimental class demonstrated a significant increase in learning interest, marked by active participation, positive social interaction, and higher learning motivation. This study extends previous research by highlighting the relevance of STAD in IPAS learning at the elementary school level and emphasizes the teacher’s role as a facilitator in creating a collaborative and engaging learning environment. STAD can serve as an alternative instructional strategy to support the implementation of the student-centered Kurikulum Merdeka.